2021
DOI: 10.1093/ntr/ntab023
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effectiveness of COVID-Related Smoking Cessation Messages in Three Countries

Abstract: Introduction Health authorities are advising smokers to quit to reduce their COVID-related risk. The types of messages that may be effective in alerting smokers to this risk and encouraging a quit attempt are unknown. The aim of this study was to test a series of messages to identify potentially effective communication approaches. Methods An online survey was completed by 1509 smokers across three countries (Australia: n = 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
3
12
0
1
Order By: Relevance
“…Exposure to the combined risk messages led to higher intentions to quit smoking in the next month (vs. COVID-19 risk) and reduce smoking in the next 6 months (vs. smoking risk and non-risk control). These results confirm and add to research where people who smoke perceived combined risk messages as more effective at discouraging smoking than generic messages ( Grummon et al, 2020 ; Pettigrew et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Exposure to the combined risk messages led to higher intentions to quit smoking in the next month (vs. COVID-19 risk) and reduce smoking in the next 6 months (vs. smoking risk and non-risk control). These results confirm and add to research where people who smoke perceived combined risk messages as more effective at discouraging smoking than generic messages ( Grummon et al, 2020 ; Pettigrew et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…Finally, each risk condition resulted in greater negative emotions and lesser positive emotions than the control condition. These results add evidence to earlier work testing smoking and COVID-19 health messages ( Grummon et al, 2020 ; Pettigrew et al, 2021 ) and inform public health communication and policy during the COVID-19 crisis, especially regarding novel strategies for motivating smoking cessation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It is also possible that due to the mixed evidence of whether it is riskier to smoke if COVID-19 was contracted [ 7 , 14 , 53 , 54 ], coupled with suggestive evidence that that nicotine could in fact be a protective factor from COVID-19 [ 54 – 56 ], smokers may be confused about the role and potential impacts of nicotine and smoking on COVID-19. Some evidence has shown that messages on COVID-related risks and smoking may be effective in encouraging a quit attempt [ 57 , 58 ], therefore stronger and accurate public health messaging should be disseminated.…”
Section: Discussionmentioning
confidence: 99%
“…Účinnější bylo znění A, tedy text apelující na úlevu zdravotníků (5). Taková aktivita v ČR chybí, existuje tu jen soukromá iniciativa www.darujluzko.cz založená na prakticky okamžitém snížení rizika akutní kardiovaskulární příhody po poslední cigaretě.…”
Section: Přístup Státuunclassified